Penyuluhan Rehabilitasi dan Konservasi Mangrove Kepada Masyarakat di Kelurahan Basilam Baru - Insusanty, Enny; Sadjati, Emy; Tri Ratnaningsih, Ambar (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2025)
Basilam Baru Village, located in Dumai City, is located on the coast of Sumatra Island facing the Malacca Strait. It has a strategic position and high potential as a mangrove ecosystem area with various flora and fauna. However, as an area located on the coast, Basilam Baru Village is vulnerable to various human activities that threaten the sustainability of the ecosystem. The methods used are counseling, planting demonstrations, evaluation and assistance. Counseling activities with Basilam Baru Village farmer group partners have increased the knowledge and understanding of partners in rehabilitation and conservation to maintain the sustainability of mangrove forests by 12.22%